Modele szkolnej edukacji moralnej wobec rozwoju kompetencji moralnych. Analiza porównawcza - Chomczyńska-Rubacha , Mariola; Rubacha, Krzysztof (Studia Edukacyjne, 2016)
The present text is a comparative analysis of models of school moral education due to the criteria of the moral competence development. We refer to the already described in the literature models: clarification of values, stimulate moral reasoning, formation of character and community justice. These models will be confronted with moral competence, which we understand as a system of knowledge of the values, skills, moral activities and taking responsibility for their actions. Results of the analysis showed that the model of community justice best meets with the criteria of moral competences.